137 An Imaging Specialist Nurse Facilitates the Expansion of the Cardiac Imaging Service. (31st May 2014) - El sayed, Hossam; Hung, John; Rashid, Muhammad; douglas, Homeyra; Burgess, Malcolm; Linnett-Cook, Carla
Abstract : Background: Stress echocardiography (SE) is a versatile and safe imaging modality used in the evaluation of coronary artery disease. The sensitivity of stress echocardiography for detection of significant coronary disease ranges from 80–90%. The risk of serious adverse events is extremely low with no reported deaths. 1 A change in NICE recommendations 2 led to a large increase in demand for stress echocardiography. Despite this, SE is still an underutilised modality, due to limited resource and operator availability. 3 Contrast echocardiography improves the image quality and diagnostic yield for assessing left ventricular systolic function. It require intravenous administration of the contrast and it can be time consuming, requiring a medical doctor to insert cannula and administer the contrast. Method: After the implementation of NICE guidelines (CG95) in 2010, we observed a 40% rise in requests for stress testing. A specialist nurse-led imaging service was introduced in April 2013. The imaging nurse was initially trained to perform the exercise stress echocardiography. After 3 months of further training with direct supervision of an imaging consultant (27 sessions), the nurse was able to perform Dobutamine stress echocardiography (DSE) with indirect supervision (total of 22 sessions). All referrals were screened, and suitability for nurse-led DSE was assessed by a consultant cardiologist. The imaging nurse was also trained to deliver contrast echocardiography; bubble echocardiography and myocardial perfusion scan. We present the data from 1st April to 1st November 2013. All the tests performed by the nurse were reported by a consultant. Results: With the introduction of an imaging nurse specialist, we are able to perform 410 imaging tests which would have otherwise been delivered by a consultant or registrar (Table 1 ). Conclusion: Introduction of a cardiac imaging nurse specialist is a safe and cost effective way of expanding the imaging service in a district general hospital. It helps with the freeing up of valuable consultants' and registrars' time for reporting images.